Sex Workers and Criminalization in North America and China Ethical and Legal Issues in Exclusionary Regimes - Dewey, Susan; Zheng, Tiantian; Orchard, Treena; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Sex work continues to provoke controversial legal and public policy debates world-wide that raise fundamental questions about the state$1 (Bs role in protecting individual rights, status quo social relations, and public health. This book unites ethnographic research from China, Canada, and the United States to argue that criminalization results in a totalizing set of negative consequences for sex workers$1 (Bhealth, safety, and human rights. Such consequences are enabled through the operations of an exclusionary regime, a dense coalescence of punitive forces that involves both governance, in the form of the criminal justice system and other state agents, and dynamic interpersonal encounters in which individuals both enforce and negotiate stigma-related discrimination against sex workers. Chapter Two demonstrates how criminalization harms sex workers by isolating their work to potentially dangerous locations, fostering mistrust of authority figures, further limiting their abilities to find legal work and housing, and restricting possibilities for collective rights-based organizing. Criminalized sex workers report police harassment, seizure of condoms, and adversarial police-sex worker relations that enable others to abuse them with impunity. Chapter Three describes how sex workers negotiate these restrictions on their rights and personal autonomy via their arrest avoidance and client management strategies, self-treatment of health issues, selective mutual aid, rights-based organizing, and entrenchment in sex work or other criminalized activities. Chapter Four describes how researchers working in countries or locales that criminalize sex work face ethical concerns as well as barriers to their work at the practical, institutional, and political levels.s
Chapter 1: Law, Public Policy, and Sex Work in North America -- Chapter 2: Systematic Collusion: Criminalization$1 (Bs Health and Safety Impacts on Sex Workers -- Chapter 3: Autonomy, Citizenship, and Resistance -- Chapter 4: Researchers$1 (BNegotiations of Systematic Collusion. .s
Keywords: Social sciences; Anthropology; Criminology; Sociology; Sex (Psychology).; Gender expression; Gender identity; Social Sciences; Anthropology; Criminology & Criminal Justice; Gender Studies; Electronic books